2018
DOI: 10.1109/jstars.2017.2784784
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Double and Single Crop Paddy Rice With Sentinel-1A at Varying Spatial Scales and Polarizations in Hanoi, Vietnam

Abstract: Paddy Rice is the prevalent land cover in the mosaicked landscape of the Hanoi Capital Region, Vietnam. In this study, we map double and single crop rice in Hanoi using a random forest algorithm and a time-series of Sentinel-1 SAR imagery at 10 and 20 m resolution using VV-only, VH-only, and both polarizations. We compare spatial and areal variation and quantify input band importance, estimate crop growth stages, estimate rice field/collective metrics using Fragstats with image segmentation, and highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 72 publications
0
65
0
Order By: Relevance
“…Regarding rice phenology, the low values of backscattering of σ • VV and σ • VH were found in the early stages such as sowing days and soil preparation, and the fallow periods in semi-dike area. it was also agreed that during sowing dates there was low backscattering [41,42,48,95]. Moreover, Oyoshi et al [92] noticed that there was low backscattering during the sowing stage and high backscattering during the maturity stage based on the unique phenological changes of rice crop using SAR data.…”
Section: Discussionmentioning
confidence: 82%
“…Regarding rice phenology, the low values of backscattering of σ • VV and σ • VH were found in the early stages such as sowing days and soil preparation, and the fallow periods in semi-dike area. it was also agreed that during sowing dates there was low backscattering [41,42,48,95]. Moreover, Oyoshi et al [92] noticed that there was low backscattering during the sowing stage and high backscattering during the maturity stage based on the unique phenological changes of rice crop using SAR data.…”
Section: Discussionmentioning
confidence: 82%
“…Analyzing the results of the confusion matrix, the total accuracy of our classification was 84% and the Kappa coefficient was 0.77. Previous research has shown that many more classification methods could improve the accuracy of crop mapping [38,39]. However, the method we chose in this case is relatively simple and sufficiently accurate.…”
Section: Mapping the Sentinel-1-derived Winter Wheat Planting Areamentioning
confidence: 99%
“…However, obtaining suitable optical satellite imagery is difficult because of the weather effects in cloudy areas [16]. To overcome the limitations of optical imagery, some studies used synthetic aperture radar (SAR) imagery to map the spatial distribution [17,18], crop height [19,20], and yield estimation of paddy rice [21][22][23]. Similar to the studies using optical imagery only, the integration of optical and SAR imagery for yield estimation also involved regression models [15,24] and artificial neural networks [25].…”
Section: Introductionmentioning
confidence: 99%